Internal, Eksternal, Bencana FAKTOR INTERNAL YANG BERPENGARUH TERHADAP FAKTOR EKSTERNAL PRA-BENCANA DI DUSUN PANDANSARI KRAJAN, DESA PANDANSARI KEC. PONCOKUSUMO KAB. MALANG - oda debora (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2017)
Abstract Resilliency and community independence are two important factors in the pre-disaster phase as it is one of the forms of disaster preparedness. Resilliency was formed from the internal society factors as well as external environmental conditions. This research aim was to find the influence of internal factors on four components of pre-disaster phase. Analysis using Partial Least Square. Result of inner estimation model for direct influence of internal factor to external showed t-statistic value equal to 3,495 (? = 0,05), so there was a significant direct positive influence between internal factor to external. The external factor with the largest loading factor was population protection (0.380). Wheareas the largest factor loading factor internal was experience repetition (0.602). The village authorized credibillity among public processed significant role in relation to the disaster management program. Experience had succeeded in changing public perception of disaster, so that disaster risk reduction program could be well implemented. Programs and activities based on community experiences and government credibillity can be developed in order to reduce disaster vulnerability. Keywords: community resilliency, natural disaster, disaster risk reduction